Democratization of Local-Self-Government in Russia: Current State and Perspectives of Development - POMAZANSKIY, Andrey; SEVALNEV, Viacheslav (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The article is devoted to the constitutional legal regulation of local self-government. The dynamics of the realization of the constitutional principles of local self-government are researched. It is outlined that the current state of legal regulation is far from the constitutional principles devoted to the local self-government. The vivid example of such regulation is the latest amendments to the Federal Law of October 6, 2003 №131-FZ ‘On General Principles of Organization of Local Self-Government in the Russian Federation’. These legislative novelties lead to phasedown of the democratic basis of local self-government. This approach shouldn’t be admitted. Its further spread to all spheres of local activities will result in the estrangement of local communities from the public authorities and officials. In this sense, the piecemeal replacement of democratic procedures in the course of formation of local authorities by the administrative ones fails to meet the legal nature of local self-government. Special attention is given to the determination the balance between representative and participatory democracy at the local level. The nature and features of local self-government are assumed the use of various organizational forms of execution of local power as well as the system of its legal regulation. Also the determination of the prospects for the extension of participatory democracy at the local level is presented.